European and Regional Integration Concepts in Poland (1789–2004) - Gedeon, Magdolna; Halász, Iván (The Development of European and Regional Integration Theories in Central European Countries, 2022)
The Polish-Lithuanian Commonwealth was one of the largest states in early Modern Europe. Its internal public law structure was complex and had several federal features. The existence of different levels of autonomy was no stranger to him. Many nations and denominations (churches) were mixed in this state, which ceased to exist at the end of the 18th century, but the ideal of independent Russians, but none of them were successful. Various concepts were born among Polish politicians; these often dealt with a Central and Eastern European federation with Polish leadership. In the first half of the 19th century, the Poles held Slavic solidarity concepts that soughtromantic intellectuals. In time, however, Slavic solidarity took a back seat. In the second half Lithuanian Commonwealth in a fairer federation. These ideas imilar time in tsarist Russia, the Polish National Democratic Party tsarist Russia and propagated the rebirth of Poland in the form of a smaller but more Polish national state. Roman Dmowski, a leader of the NDP, had a conflict with Piłsudski that was big state with regional ambitions, but it had two dangerous neighbors—Nazi Germany and the Soviet Union. The Polish leaders therefore had to think about various federal alternatives, most of which revolved around solidarity in Central and Eastern Europe. Such were the Intermarium or Jagellonian plans. The Polish tragedy during the Second World War and Soviet dominance after 1945 only reinforced these ideas. Many Polish intellectuals began to see the future in European unity, although such ideas existed as early as the 19th century. Some of the Polish emigration to Paris worked to reconcile them with the peoples of Eastern Europe (Ukrainians, Lithuanians, and Belarusians). The journal Kultura played the crucial role in this process. Poland after 1989 again plays an important European role in three regional contexts: Central Europe, the Baltic Sea, and North-Eastern Europe.KEYWORDS: Baltic sea, Central Europe, federation, Polish-Lithunian Commonwealth, Ukraine